The Fundamental of Group Behavior and Teamwork Through the Perspective of PAUD Tunas Harapan Accreditation Assessment - Siswanto, Roni; Wicaksono, Luhur; Waruwu, Marinu (Universitas Negeri Jakarta, 2024)
Background: PAUD Tunas Harapan, an early childhood education center, faces challenges in improving educational quality through the accreditation process, which relies heavily on group dynamics and teamwork among educators and staff. Ineffective team coordination often hinders the institution from meeting required standards. Purpose: This study aims to examine the impact of group behavior and teamwork on accreditation quality at PAUD Tunas Harapan and to identify factors and strategies that support the team’s success in achieving accreditation standards. Design/method/approach: A qualitative case study approach was employed, involving in-depth interviews and observations with the school principal, teachers, and accreditation assessors. Data were analyzed thematically to identify patterns in group behavior and team dynamics. Results: The findings reveal that structured communication, collaborative leadership, regular evaluations, and a shared vision are key factors in improving accreditation quality. Effective coordination and collaboration were shown to help overcome challenges and enhance team productivity. Contribution/value: This study contributes insights into the application of group dynamics and teamwork theories in early childhood education settings. The recommendations provided may assist PAUD and similar institutions in improving accreditation quality through more adaptive and collaborative team strategies.